Comparative study of the impact of defense expenditure on economic growth in China and US. (18th August 2018) - Sida, Peng; Zhe, Liu
Abstract: The correlation between defense expenditure and economic growth has been deeply researchedwhose results fail to reach a clear consensus. This paperstudies the impact of defense expenditure on economic growth in China and US. In order to identify not only long-term but also short-term effect among variables, we respectively use the autoregressive distributive lag bounds testing (ARDL) and the vector error correction model (VECM). The research results show that as for US, an obvious positive effect of defense expenditure on economic growth has been found in both short and long term. On the contrary, when it comes to China, the impact of defense expenditure on economic growth is not remarkable.